2018
DOI: 10.1016/j.jid.2017.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Screen for MicroRNAs Reveals a Role for miR-203 in Melanoma Metastasis

Abstract: Melanoma is one of the deadliest human cancers with limited therapeutic options. MicroRNAs are a class of short noncoding RNAs regulating gene expression at the post-transcriptional level. To identify important miRNAs in melanoma, we compared the miRNome of primary and metastatic melanomas in The Cancer Genome Atlas dataset and found lower miR-203 abundance in metastatic melanoma. Lower level of miR-203 was associated with poor overall survival in metastatic disease. We found that the methylation levels of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 35 publications
(32 reference statements)
1
31
0
Order By: Relevance
“…In addition, PLEKHA7 re-expression results in the increased levels of miRNAs that we have previously identified to be regulated by PLEKHA7 in Caco2 cells, such as miR-30b, miR-200c, and miR-203a ( Figure 5I) [10,25]. These miRNAs are well-established tumor suppressors and are downregulated in many cancers, including colorectal tumors, as well as in colon cancer cell lines, such as those included in our study [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Together, these results are in agreement with our previous findings [10,25] and further support a tumor suppressing role for PLEKHA7 in the colonic epithelium, through recruitment and regulation of the RNAi machinery.…”
Section: Plekha7 Re-expression In Hct116 Cells Restores Junctional Lomentioning
confidence: 57%
“…In addition, PLEKHA7 re-expression results in the increased levels of miRNAs that we have previously identified to be regulated by PLEKHA7 in Caco2 cells, such as miR-30b, miR-200c, and miR-203a ( Figure 5I) [10,25]. These miRNAs are well-established tumor suppressors and are downregulated in many cancers, including colorectal tumors, as well as in colon cancer cell lines, such as those included in our study [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Together, these results are in agreement with our previous findings [10,25] and further support a tumor suppressing role for PLEKHA7 in the colonic epithelium, through recruitment and regulation of the RNAi machinery.…”
Section: Plekha7 Re-expression In Hct116 Cells Restores Junctional Lomentioning
confidence: 57%
“…miR-182, miR-200c and miR-205 expression levels did not correlate with any TCGA transcriptomic subtypes. In an in silico analysis using the TGCA database, Lohcharienkal et al 33 also found a decreased expression of miR-200c and miR-182 in primary vs metastatic melanomas. These findings agree with our observations, since miR-200c and miR-182 expression were significantly decreased in the different stages of melanoma progression.…”
Section: Discussionmentioning
confidence: 97%
“…Based on its their reported functionality, demonstrated target genes and expression pattern during chick development (Darnell et al, 2006), we further focused on miR-203 for in depth analysis. Importantly, miR-203 has been described to act as tumor suppressor (Benaich et al, 2014, Miao et al, 2014, Zhu et al, 2013b), that directly regulates Snail2 expression (Gao et al, 2017, Shi et al, 2015, Zhang et al, 2015, Xiao et al, 2017), whose epigenetic repression causes metastasis in several tumor cells including NCC-derived melanoma (Boldrup et al, 2012, Boll et al, 2013, Chen et al, 2012, Chiang et al, 2011, Ding et al, 2013, Furuta et al, 2010, Huang et al, 2014, Ju et al, 2014, Moes et al, 2012, Zhang et al, 2014, Zhao et al, 2013, Bu and Yang, 2014, Lohcharoenkal et al, 2018). Moreover, the mature miR-203 sequence is highly conserved throughout vertebrates including the basal lamprey (Fig.…”
Section: Resultsmentioning
confidence: 99%